2007
DOI: 10.1016/j.jneuroim.2007.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Short-term sPECAM-Fc treatment ameliorates EAE while chronic use hastens onset of symptoms

Abstract: The homotypic cell adhesion molecule PECAM-1 is a major participant in the migration of leukocytes across endothelium. We examined the ability of a chimeric soluble sPECAM-1 fused to human IgGFc to impair leukocyte entry through the blood-brain barrier and reduce CNS autoimmunity. sPECAM-Fc impaired migration of lymphocytes across brain endothelial monolayers and diminished the severity of EAE, an experimental model of MS, when administered at the onset of symptoms. However, in mice transgenic for sPECAM-Fc, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…The effects of blocking CD31 with antibodies are consistent with an adhesive function of this molecule as antibodies to CD31 have been shown to reduce leukocyte infiltration and disease severity dramatically in in vivo models of T-cell-mediated inflammation, including collagen-induced arthritis (CIA) (Ishikaw et al, 2002); (Decking et al, 2001) and experimental autoimmune encephalitis (Qing et al, 2001); (Bogen et al, 1994;Liao et al, 1997;Reinke et al, 2007;Vaporciyan et al, 1993).…”
Section: Molecular Mechanisms Of Differential Cd31 Activity In Naïve mentioning
confidence: 85%
See 1 more Smart Citation
“…The effects of blocking CD31 with antibodies are consistent with an adhesive function of this molecule as antibodies to CD31 have been shown to reduce leukocyte infiltration and disease severity dramatically in in vivo models of T-cell-mediated inflammation, including collagen-induced arthritis (CIA) (Ishikaw et al, 2002); (Decking et al, 2001) and experimental autoimmune encephalitis (Qing et al, 2001); (Bogen et al, 1994;Liao et al, 1997;Reinke et al, 2007;Vaporciyan et al, 1993).…”
Section: Molecular Mechanisms Of Differential Cd31 Activity In Naïve mentioning
confidence: 85%
“…In support of this interpretation, transgenic mice that chronically express high levels of circulating recombinant CD31 molecules (sPECAM-Fc) develop an earlier onset of EAE (Reinke et al, 2007). It is tempting to speculate that an overly high concentration of circulating CD31 ligand might have prevented CD31 signaling in T-cells by interfering with CD31 clustering, an effect known to occur in the presence of over-saturating concentrations of T-cell-stimulating antibodies (Roosnek et al, 1987).…”
Section: Molecular Mechanisms Of Differential Cd31 Activity In Naïve mentioning
confidence: 99%
“…In order for macrophages to migrate to the CNS and induce damage, they must follow a chemotactic gradient stemming from the source of activity [36]. In EAE, it has been shown that tissues up-regulate the expression of multiple chemokines, thereby inducing cellular recruitment [15,30,37]. Moreover, studies conducted on EAE pathogenesis implicate a few specific chemokines in the induction of EAE [12].…”
Section: Discussionmentioning
confidence: 99%
“…Tumor cell invasiveness was measured with a Transwell system (BD Biosciences, San Jose, CA, USA) [22]. The cells were treated with different concentrations of QGS (0, 50, or 100 μg/mL) for 24 h. The …”
Section: Invasion Assaysmentioning
confidence: 99%